2015
DOI: 10.3354/ab00625
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sublethal effects of oil, chemical dispersant, and dispersed oil on the ctenophore Mnemiopsis leidyi

Abstract: We established the lethal levels for water-accommodated fractions of Corexit ® 9500A chemical dispersant, crude oil (WAF), and dispersed crude oil (CEWAF) for the ctenophore Mnemiopsis leidyi at both 15 and 23°C. This gelatinous zooplankter was sensitive to dispersant at both temperatures, as well as to oil solutions, with some increase in toxicity of CEWAF as compared to WAF. Subsequent sublethal assays for routine respiration rate, bioluminescence, and glutathiones-transferase (GST) activity were conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…For an insensitive species, toxic units are below 1 at the highest loading evaluated, indicating that a 50% lethal response would not be obtained for this oil (e.g., LL50 >1000 mg/L). Recent studies using a variable loading test design reported acute 48‐h LL50s for Macondo oil based on WAF/chemically enhanced WAF (CEWAF) test exposures using a marine copepod ( Labidocera aestiva ) in the range of 3.3 to 5.0 mg/L and the comb jelly ( Mnemiopsis leidyi ) in the range of 6.7 to 29.5 mg/L (Cohen et al ; Peiffer and Cohen ). These measured acute toxicity data are within the predicted range expected from Figure for moderately sensitive species.…”
Section: Resultsmentioning
confidence: 99%
“…For an insensitive species, toxic units are below 1 at the highest loading evaluated, indicating that a 50% lethal response would not be obtained for this oil (e.g., LL50 >1000 mg/L). Recent studies using a variable loading test design reported acute 48‐h LL50s for Macondo oil based on WAF/chemically enhanced WAF (CEWAF) test exposures using a marine copepod ( Labidocera aestiva ) in the range of 3.3 to 5.0 mg/L and the comb jelly ( Mnemiopsis leidyi ) in the range of 6.7 to 29.5 mg/L (Cohen et al ; Peiffer and Cohen ). These measured acute toxicity data are within the predicted range expected from Figure for moderately sensitive species.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding vulnerability to toxins, we do know that both crude oil and dispersants can have deleterious effects on crustaceans. both lethal and sublethal, including altered reproduction, respiration rates, growth, feeding and locomotion (Almeda et al, 2013a;Peiffer and Cohen, 2015). One study that tested the effects of crude oil (specifically, 1-methylnaphthalene) on deep-sea crustaceans showed a higher sensitivity than that expressed in coastal species (Knap et al, 2017).…”
Section: Deep-pelagic Macrocrustaceansmentioning
confidence: 99%
“…Bioaccumulation of PAHs documented in the mesoplankton community increased by 35%. The conclusion was that oil spills negatively impact mesozooplankton (Almeda et al, 2014a) and also ctenophores (Peiffer and Cohen, 2015), and this effect increases with the use of chemical dispersants and coincident exposure to UV radiation.…”
Section: Monitoring Toxicological Impacts In the Fieldmentioning
confidence: 99%